2018
DOI: 10.1097/ijg.0000000000000830
|View full text |Cite
|
Sign up to set email alerts
|

The Short-term Effect of Subtenon Sponge Application Versus Subtenon Irrigation of Mitomycin-C on the Outcomes of Trabeculectomy With Ex-PRESS Glaucoma Filtration Device: A Randomized Trial

Abstract: Application of subtenon MMC by irrigation seems to provide improved short-term outcomes compared with application with sponges. With a similar safety profile, the irrigation method provides better IOP control, and decreases the need for further clinical/surgical intervention in the short-term after trabeculectomy. Longer-term studies will be useful in analyzing if these differences persist with time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 32 publications
1
20
2
Order By: Relevance
“…Other studies of MMC injection or irrigation with trabeculectomy surgery in human eyes likewise show similar mean IOP outcomes in comparison to sponge groups as well as no statistically significant difference in success rate of IOP control. 21,23,27 However, 1 study did find a significantly greater change in IOP from baseline in the MMC irrigation group at postoperative month 6 in comparison to the MMC sponge group in eyes treated with trabeculectomy and EX-PRESS shunt. 23 Our study revealed a surprising finding in that trabeculectomy surgeries performed with limbus-based conjunctival incisions had a longer time to failure for IOP control.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Other studies of MMC injection or irrigation with trabeculectomy surgery in human eyes likewise show similar mean IOP outcomes in comparison to sponge groups as well as no statistically significant difference in success rate of IOP control. 21,23,27 However, 1 study did find a significantly greater change in IOP from baseline in the MMC irrigation group at postoperative month 6 in comparison to the MMC sponge group in eyes treated with trabeculectomy and EX-PRESS shunt. 23 Our study revealed a surprising finding in that trabeculectomy surgeries performed with limbus-based conjunctival incisions had a longer time to failure for IOP control.…”
Section: Discussionmentioning
confidence: 87%
“…21,23,27 However, 1 study did find a significantly greater change in IOP from baseline in the MMC irrigation group at postoperative month 6 in comparison to the MMC sponge group in eyes treated with trabeculectomy and EX-PRESS shunt. 23 Our study revealed a surprising finding in that trabeculectomy surgeries performed with limbus-based conjunctival incisions had a longer time to failure for IOP control. The literature regarding the effect of conjunctival incision type on post-trabeculectomy IOP outcomes is mixed.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations